Statistical analysis of shear strength tests adhesivly bonded cylindtcal joints - Zielecki, Władysław; Bielenda, Przemysław (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2019)
The article describes the influence of selected structural factors such as joint length, thickness of the adhesive layer, the size of the phase in the bush ing open ing and the surface roughness on the shear strength of adhesivly bonded cylindrical joints. The Minitab program was used to carry out the necessary analyzes. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)